INTEGRATED ISLAMIC SCHOOL MARKETING STATEGIES THROUGH THE INTERNET IN 4.0 ERA - Muhammad Sajirun; Lin Yan Syah (Dinasti Publisher, 2020)
The In the 21 st century and move on in 4.0 era, it has avery significant impact and influence on marketing trends, not least in the world of education that carries social values (non-profit). Tren marketing trend is shifting and even shifting from conventional (offline) to digital (online). For business people, the concept of digital marketing is very helful for marketing products across regions and countries, from anywhere and anytime through the internet, so with education institutions can market school excellence (brand awareness) trough the internet. Focus of the issues raised are: (1) How brand awareness strategy trough digital marketing is carried out by the integrated Islamic school Syajarul Qur’an (2) What are the obstacles and benefits of implementating digital marketing for integrated Islamic Schools Syajarul Qur’an Gelumbang / Muara Enim. To deepen and reveal the above problems the researcher will use qualitative research which is of course very useful for investigations in order to provide facts and data regarding the implementation of digital marketing barand awareness of integrated Islamic Schools that we meanbove. Then the data obtained will be abalyzed with the groundes theory approach which provides development of the field of reaserch studies. Then the data collection techniques using interview, documentation and observation. Data reduction techniques namely sharping, classifying, directing, organizing, data and removing unnecessary data, verification, data presentation and drawing conclusions. While the theory used in this study is the theory of brand awareness strategy implementation which means how far the implementation of digital marketing for stakeholder satisfaction as well as how far the image formed influences prospective customers decisions. From the results of preliminary research conducted by researchers found that the brand awareness strategy trough digital marketing the school delivered a positioning statement in each facebook post, whatApp and instagram groups and established relationships with customers in a past respond in the medisocial which is used and which is not important is involving a third party (sisko) to deliver school information concerning: Managerial Service: (Teacher Assessment, Education Calender, Library, Inventory and Administration). Finacial Service: (Montly finance, Cash Flow, e-Money, and recep of financial records) Teaching Service: ( Curriculum, Syllabus and RPP, report cards and assement, Guidance Counceling, extracurricular) Communication Service: (Communication Book, Polls, School News, Announcements, Branding tool). The obstacles and benefits of implementating digital marketing related to wifi systems that are less supportive. Suggestions for school managers to continue to run school marketing with conventional (customer centric) and remain consistent in marketing brand awareness through digital marketing developing digital marketing based on clusters (age cluster, domiciles) and other.